Seismic Control of Power Transmission Tower Using Pounding TMD - Zhang, Peng; Song, Gangbing; Li, Hong-Nan; Lin, You-Xin (Journal of engineering mechanics, 2013)
AbstractLattice transmission towers are vital components of transmission line systems, which play an important role in the operation of electrical power systems. This paper proposes a new type of tuned mass damper (TMD), the pounding tuned mass damper (PTMD), to upgrade the seismic resistant performance of a transmission tower. In the PTMD, a limiting collar with viscoelastic material laced on the inner rim is installed to restrict the stroke of the TMD and to dissipate energy through collision. The pounding force is modeled based on the Hertz contact law, whereas the pounding stiffness β is estimated in a small-scale test. A multimass model of a 55-m tower is established to verify the effectiveness of the PTMD numerically. Harmonic excitation and time-history analysis demonstrate the PTMD’s superiority over the traditional TMD. Finally, a parametric study is performed for the optimal design.